Impact of Clinical Factors on Generic and Disease-Specific Quality of Life in COPD and Asthma-COPD Overlap with Exacerbations - Lázár, Zsófia; Horváth, Alpár; Tomisa, Gábor; Tamási, Lilla; Müller, Veronika (Pulmonary Medicine, 2020)
Purpose. The health-related quality of life (HRQL) in chronic obstructive pulmonary disease (COPD) is worsened by frequent exacerbations, and it can be affected by the concomitant presence of bronchial asthma (asthma-COPD overlap (ACO)). The impacts of clinical factors associated with HRQL have not been compared in patients with COPD and ACO experiencing exacerbations. Patients and Methods. Patients with COPD (N =705) and ACO (N =148) belonging to C and D groups according to GOLD 2017 were recruited in stable condition. Demographic and clinical data were collected, spirometry was performed, and patients rated the intensity of respiratory symptoms during the previous week. The COPD Assessment Test (CAT) and the EQ-5D 3 level version (dimensions and visual analogue scale (VAS)) were used to assess disease-specific and generic HRQL, respectively. Fisher’s exact test, χ2 test, ANOVA, and Pearson correlation were used for analysis (mean±SD). Multiple linear regression was applied to identify variables related to CAT and EQ-5D VAS scores. Results. The CAT and EQ-5D VAS scores showed similarly low HRQL in COPD and ACO (20.7±6.7 vs. 21.1±6.3 (p=0.52) and 56.2±17.8 vs. 53.7±18.2 (p=0.11)). There was a weak correlation between CAT and EQ-5D VAS scores (COPD: r=−0.345, p<0.001; ACO: r=−0.245, p=0.003). More patients with COPD had problems related to anxiety/depression in EQ-5D (63.7% vs. 55.4%, p=0.06). Pack-years exerted a negative effect on HRQL measures both in ACO and COPD. Low HRQL in COPD was associated with female gender, dyspnea, cough, gastroesophageal reflux disease, and arrhythmia, while in ACO, it was related to arrhythmia, hypertension, and cough, but less to dyspnea. Conclusions. Patients with COPD and ACO experiencing exacerbations have low quality of life, which is influenced by smoking history, symptoms, and comorbidities. These findings have important implications for the development of therapeutic strategies to improve the health status of patients with these conditions.